A population-based study on the association between the intake of soft drinks and periodontal disease in Taiwanese adults aged 35–44 years (KCIS no. 33). Issue 8 (9th September 2015) - Fann, Jean Ching-Yuan; Lai, Hongmin; Chiu, Sherry Yueh-Hsia; Yen, Amy Ming-Fang; Chen, Sam Li-Sheng; Chen, Hsiu-Hsi
Abstract: Objective: To elucidate the association between the intake of soft drinks and periodontal disease (PD) among Taiwanese middle-aged adults. Design: The cross-sectional design was employed to assess a dose–response relationship between the intake of soft drinks and PD after controlling for relevant confounding factors, with adjusted odds ratios obtained from a multivariate logistic regression model. Setting: Keelung Community-based Integrated Screening (KCIS) programme, Keelung, Taiwan. Subjects: Participants ( n 10 213) aged 35–44 years who had undergone oral checks for PD between 2005 and 2009. Results: A dose–response relationship between the intake of soft drinks and elevated risk for PD defined by community periodontal index ≥3 (the current status of PD) was noted ( P =0·02 by trend test). Compared with infrequent intake of soft drinks (≤2 times/week), the adjusted OR increased from 1·05 (95 % CI 0·92, 1·20) for the frequency of 3–4 times/week to 1·17 (95 % CI 1·03, 1·34) for the frequency of ≥5 times/week. A similar trend ( P <0·01) was also observed for PD defined by loss of attachment ≥1 (representing the long-term cumulative gum damage due to PD). Conclusions: A dose–response relationship between the intake frequency of soft drinks and PD was observed in Taiwanese middle-aged adults. Such evidence could be used in health promotion to support reductions in soft drink intake.